Identification of structural domains within the cauliflower mosaic virus movement protein by scanning deletion mutagenesis and epitope tagging. - Thomas, C L (1995)
Plant viruses encode proteins that mediate their movement from cell to cell through plasmodesmata. Currently, the mechanisms of action of these movement proteins (MPs) can be divided broadly into two types, requiring or not requiring the presence of viral capsid protein. Cauliflower mosaic virus encodes a multifunctional MP (P1) that modifies plasmodesmata through the formation of tubules that contain virus particles. To investigate the structure of P1, 26 small deletions (scanning deletions) were used to characterize regions of P1 essential for full biological activity. These deletions identified an N-terminal region and a region close to but not at the C terminus as domains that could tolerate manipulation, although gross deletions of either domain abolished infection. In sequence comparisons with other caulimovirus MPs, these regions coincided with the areas of least amino acid homology. Epitope tags inserted into either of these regions were stably maintained in systemic infections, and in extracts from infected plants, tagged P1 was detected on immunoblots. We predicted that, from the hypervariability of these regions, they would be located on the surface of the native P1 structure. Immunofluorescence of P1-specific tubules formed on the surface of infected protoplasts confirmed that the N-terminal and C terminus-proximal regions were exposed on the surface of the P1 tubule subunit. These findings establish a structure for P1 that is likely to be applicable to other tubule-forming MPs.